Motivasi Pembelajaran Jarak Jauh dengan Buku Saku Tematik Berbasis Model Pembelajaran ARCS - Ubaidillah, Ahmad; Suad, Suad; Santosa, Santosa (Universitas PGRI Semarang, 2023)
Distance learning that elementary students must take during this pandemic is a new procedure in the learning mechanism in Indonesia. However, the course of learning activities has not been able to run effectively. Less developed learning atmosphere is caused by low student motivation due to internal factors such as reading interest in learning resources in the form of textbooks and little teacher explanation. The objectives of this research and development are: 1) Analyzing the trial results of thematic pocket book products before they are developed to improve social studies learning motivation, 2) Analyzing the development of thematic pocket books based on the ARCS learning model to increase social studies learning motivation, 3) Analyzing the effectiveness test of using books thematic pocket based on ARCS learning model to increase social studies learning motivation. This research is a Research and Development (R D) method with the Sugiyono level 3 method. This research was conducted in ten steps, namely: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product testing, 7) product revision. 8) trial and error, 9) product revision, 10) mass production.